Fish Gut Metabarcoding Detects Diets and Parasites Simultaneously - Dilli Prasad Rijal; Per Arneberg; Tanja Hanebrekke; Torild Johansen; Daniela Sint; Michael Traugott; Mette Skern‐Mauritzen; Jon‐Ivar Westgaard (Environmental DNA)
ABSTRACT Understanding the dietary habits and trophic niches of species is crucial for the conservation and management of species and ecosystems. Science‐based fisheries management requires large‐scale data of prey and parasites of fish species that enables the analysis of multitrophic interactions in an ecosystem. Using one of the commercially exploited beaked redfish (Sebastes mentella) from the Barents Sea, our study aims to understand its diet composition and parasites. We used 12S and COI markers to analyze the stomach and intestine contents of uncleaned, water‐cleaned, and bleach‐cleaned fish samples to also trace how external contamination affects diet analysis of fishes. We detected 19 potential prey taxa each of vertebrates and invertebrates from the guts of beaked redfish. While invertebrates were the major food source of redfish, our analysis indicated only two taxa of vertebrates that significantly contributed to the diet composition. In addition, we also detected two jellyfish species which were among the dominant prey taxa. Several parasites that have been frequently reported from redfish by visual examination were also detected by metabarcoding of gut contents. As in metabarcoding studies in general, it is important to build the reference libraries of fish parasites to fully harness the power of molecular approaches in achieving multi‐trophic interactions. We underscore that metabarcoding captures both the common prey as well as delicate taxa which may not be available for visual examinations such as jellyfishes or other cryptic taxa. Our study showcases the importance of gut metabarcoding in terms of simultaneous detection of diets and parasites.